Isokinetic muscle strength cannot be related to the odds ratio of musculoskeletal injuries in young elite wrestlers - Hoseini, A.; Zarei, M.; Nobari, H.; Hovanloo, F.; Abbasi, H.; Pérez-Gómez, J. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background Wrestling is considered one of the oldest sports in the world. There is a high rate of injuries in Wrestling. To prevent injuries, it is necessary to identify the risk factors. Despite the functional importance of strength in wrestling, few studies have investigated the relationship between isokinetic strength and the rate of injuries in the sport.